Internalisasi Nilai-Nilai Ekonomi Islami Dalam Qs. Adz-Dzariyat Ayat 15–19 Serta Implikasinya Terhadap Pembentukan Motivasi Dan Perilaku Ekonomi Masyarakat Muslim - Nur Della, Rissa Ajeng; Izzah, Ni'matul; Maulidia, Hidayatul; In, Churin (Universitas Muhammadiyah Sumatera Utara, 2025)
This research aims to analyze the internalization of Islamic economic values in QS. Adz-Dzariyat verses 15–19 and its implications for the formation of motivation and economic behavior in Muslim society. Through a literature study approach, this research analyzes the meaning of the verses, which emphasize the balance between spirituality and social responsibility in economic activities. Values such as sincerity, justice, and concern for others serve as the foundation for forming ethical and just economic behavior. The results indicate that the internalization of Islamic economic values can encourage people to behave economically in a sustainable manner, oriented toward blessings, and to avoid economic practices that harm others. Thus, the economic values contained in QS. Adz-Dzariyat verses 15–19 are not only normative but also applicable in building a just and humanistic Islamic economic system.